Affordable Housing Without Public Subsidies: Rent-Setting Practices in Small Rental Properties. Issue 1 (2nd January 2021) - Decker, Nathaniel
Abstract: Problem, research strategy, and findings: Rental housing affordability is a severe problem for low- and moderate-income families across the United States. While some renters benefit from subsidies or rent regulation, most low-income renters live in unsubsidized, unregulated units, particularly in low-cost 1- to 4-unit properties. Some of these small rental properties are low cost because they are low quality or are in low-demand neighborhoods, but there has long been speculation that many of these units are low cost because their owners set rents below market. However, the extent to which owners set rent below market, which owners do so, and why, is unknown. I conducted a nationwide survey with follow-up interviews of the owners of small rental properties to understand below-market rent setting. I find that nearly half of small rental owners choose to set rents below market. These discounts are substantial, averaging 16% below market. Owners' rent-setting strategies are diverse, and there do not appear to be sharp distinctions between owners who set rent below market and those who do not. However, there is evidence that some owners' lack of knowledge of market conditions contributes to discounts, as does owners' impressions of their tenants' incomes. Takeaway for practice: Most municipalities likely have large stocks of good-quality below-market rental housing in small rental properties. Supporting below-market small rentals could be a means for municipalities to realize their housing affordability goals. However, the right policies to support this part of the stock are unclear and likely vary by jurisdiction. Planners could examine the owners and tenants of small rentals in their area to understand their needs and respond accordingly. Supporting this stock will raise new equity questions, particularly regarding who gets to rent these units and practical issues about how the public sector can productively engage with nonprofessional landlords.